Unintended pregnancy, contraceptive use, and childbearing desires among HIV-infected and HIV-uninfected women in Botswana: across-sectional study. (December 2015) - Mayondi, Gloria; Wirth, Kathleen; Morroni, Chelsea; Moyo, Sikhulile; Ajibola, Gbolahan; Diseko, Modiegi; Sakoi, Maureen; Magetse, Jane; Moabi, Kebaiphe; Leidner, Jean; Makhema, Joseph; Kammerer, Betsy; et al.
Abstract Background Little is known about the impact of knowledge of HIV serostatus on pregnancy intention and contraceptive use in high-HIV-burden southern African settings in the era of widespread antiretroviral treatment availability. Methods We analyzed interview data collected among 473 HIV-uninfected and 468 HIV-infected pregnant and recently postpartum women at two sites in southern Botswana. Participants were interviewed about their knowledge of their HIV status prior to pregnancy, intendedness of the pregnancy, contraceptive use, and future childbearing desires. Results The median age of the 941 women was 27 years, median lifetime pregnancies was 2, and 416 (44 %) of pregnancies were unintended. Among women reporting unintended pregnancy, 36 % were not using a contraceptive method prior to conception. Among contraception users, 81 % used condoms, 13 % oral contraceptives and 5 % an injectable contraceptive. In univariable analysis, women with unintended pregnancy had a higher number of previous pregnancies (P  = <0.0001), were less educated (P  = 0.0002), and less likely to be married or living with a partner (P  < 0.0001). Thirty-percent reported knowing that they were HIV-infected, 48 % reported knowing they were HIV-uninfected, and 22 % reported not knowing their HIV status prior to conception. In multivariable analysis, women who did not know their HIV status pre-conception were more likely to report their pregnancy as unintended compared to women who knew that they were HIV-uninfected (aOR = 1.7; 95%CI: 1.2-2.5). After controlling for other factors, unintended pregnancy was not associated with knowing one's HIV positive status prior to conception (compared with knowing one's negative HIV status prior to conception). Among women with unintended pregnancy, there was no association between knowing their HIV status and contraceptive use prior to pregnancy in adjusted analyses. Sixty-one percent of women reported not wanting any more children after this pregnancy, with HIV-infected women significantly more likely to report not wanting any more children compared to HIV-uninfected women (aOR = 3.9; 95%CI: 2.6-5.8). Conclusions The high rates of reported unintended pregnancy and contraceptive failure/misuse underscore an urgent need for better access to effective contraceptive methods for HIV-uninfected and HIV -infected women in Botswana. Lower socioeconomic status and lack of pre-conception HIV testing may indicate higher risk for unintended pregnancy in this setting.